Development of Augmented Reality (AR) Physics Learning Media Based on STEM-R for Students’ Concept Understanding - Sabilatul Khoiriyah; Sri Latifah; Vandan Wiliyanti (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
Learning media that can overcome students' difficulties in understanding abstract concepts through the integration of modern technology with character values is challenging. This study aims to develop, determine the feasibility, student response, and effectiveness of STEM-R-based AR media on concept understanding in heat temperature material. This research uses Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection was conducted through interviews, expert validation, and pretest-posttest. The validation results showed that the media was feasible for use based on the assessments of media experts, subject matter experts, and religious experts in the feasible category. The average concept comprehension scores of students in both schools showed an increase. Small-scale tests and field tests of student responses in both schools showed a very good category. The validity level of STEM-R-based AR media on students' concept comprehension is interpreted as feasible for use, and student responses to this learning media are also very good, reflecting an increase in motivation and involvement in the teaching and learning process. This research is expected to strengthen the integration of religious values in modern science learning and serve as a reference for the development of AR media based on Islamic values.